Effects of Liquid Smoking on the Microbiological and Physicochemical Characteristics of Suan Yu, a Traditional Chinese Fermented Fish Product. Issue 3 (16th March 2021) - Zeng, Xuefeng; Yang, Qin; Zhang, Wei; Liu, Jingui; He, Laping; Deng, Li; Guo, Xu
ABSTRACT: This work studied the changes in microbiological and physiochemical properties during the fermentation of Suan yu by liquid smoking and traditional smoking (batches B, C, and A). Lactobacillus plantarum, Pediococcus pentosaceus, Saccharomyces cerevisiae, and Hansenula polymorpha were the dominant microorganisms in the three samples. Only the acid-resistant Staphylococcus xylosus and Staphylococcus carnosus survived in the acid environment of the final fermented products. The amounts of Enterobacteriaceae, Enterococci, and Pseudomonades in the final fermented products were under the detection limit. Batch B and C samples had higher rate of reduction in pH (4.24 ± 0.17–4.39 ± 0.18 from 6.21 ± 0.24, respectively) and lower acetic acid generation rate (0.06%±0. 00% and 0.05%±0. 00%, respectively) than batch A samples. Large amounts of free amino acids were generated during the fermentation of the samples. Batches B and C had thiobarbituric acid reactive substances (TBARS) value between 0.88 ± 0.03 and 0.89 ± 0.03, total volatile basic nitrogen (TVB-N) value between 18.9 ± 0.34 and 18.8 ± 0.33 mg/kg, and benzo(a)pyrene (BaP) content of 0.1 ± 0.00 μg/kg, which was lower than those of fermented Suan yu prepared by traditional smoking. Sensory analysis indicates that these sample groups have unique smoking and fermentation flavor. Consequently, the fermented Suan yu produced through liquid smoking is a kind of fermented aquatic product with full-bodied smoking flavor, palatable acid flavor, abundant nutrition, and high safety.